2021
DOI: 10.1186/s12933-021-01250-5
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolism, bleeding and vascular death in nonvalvular atrial fibrillation patients with type 2 diabetes receiving rivaroxaban or warfarin

Abstract: Background Diabetes increases a patient’s risk of developing atrial fibrillation by 49%. Patients with nonvalvular atrial fibrillation are at a fivefold increased risk of stroke and die more frequently from vascular causes. We sought to evaluate the effectiveness and safety of rivaroxaban versus warfarin in nonvalvular atrial fibrillation patients with type 2 diabetes. Methods This was an analysis of Optum® De-Identified electronic health record da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…This prevents these outliers from dominating the analysis and decreasing precision (a concern when using inverse probability weighting). It also has the favorable property of resulting in the exact balance of all variables included in the logistic regression model used to derive the propensity scores [15][16][17][18].…”
Section: Propensity Score-overlap Weightingmentioning
confidence: 99%
“…This prevents these outliers from dominating the analysis and decreasing precision (a concern when using inverse probability weighting). It also has the favorable property of resulting in the exact balance of all variables included in the logistic regression model used to derive the propensity scores [15][16][17][18].…”
Section: Propensity Score-overlap Weightingmentioning
confidence: 99%
“…This method has been shown in previous observational studies to provide vascular mortality rates similar to those reported in “like” randomized controlled trials. 8 Third, the EHR data set utilized for this study included only US patients. 11 Our results may be less generalizable to populations outside the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previously published realworld evidence studies demonstrated similar or improved effectiveness and safety of rivaroxaban versus warfarin in obese patients with NVAF [35][36][37][38][39]. Studies have also demonstrated the effectiveness and safety of rivaroxaban in patients with NVAF and concurrent diabetes [34,[40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%